Estimativas da evopotranspiração da cultura por diferentes métodos, em pomar de Manga Rosa na região nordeste do Estado do Pará - MONTEIRO, Willian Bruno da Costa (2020)
Knowing the importance of the Amazon as a holder of large water resources, studies are needed to quantify how much this region loses water to the atmosphere through evapotranspiration and for this, it is essential to know what the best method that can represent this important component of the cycle. Natural hydrological. The main objective of this study was to evaluate the performance of different methods in estimating Real Evapotranspiration (ETR) in a pink mango orchard (cv Tommy Atkins), located at the “Modesto Rodrigues” Coastal Studies Experimental Site (Lat. 0 ° 39 ' 55 '' S and Lon. 47 ° 17'7 '' O), in Cuiarana, Salinópolis, northeastern Pará State. The methods analyzed were: Penman-Monteith (FAO), Hargreaves-Samani, Jensen -Haise, Priestley & Taylor, Camargo and Penman Original. The Penman-Monteith (FAO) method was used as a reference for the estimates analyzed by the other methods. Weather data for Temperature and Relative Humidity, Wind Speed, Global Solar Radiation, and Radiation Balance were measured using sensors connected to a datalogger data acquisition system (CR1000, Campbell Scientific, Inc.), installed in a micrometeorological tower. with height of 15 meters. ETR values were compared by linear regression analysis. To evaluate the performance of the models, the standard error estimation, correlation coefficient (R), determination coefficient (R²), agreement index (d) and confidence or performance index (c) were used. The semiannual, seasonal and annual analyzes refer to 2012. The results showed that the best estimates occurred in the semiannual period compared to the seasonal and annual periods, emphasizing that in the individual comparison of the estimates with the standard method, the Penman method Original was the one that presented high performance and the Hargreaves-Samani method, low performance. However, although Priestley & Taylor's method used few meteorological variables in the estimation formula, its performance was highly satisfactory.